"Telling of olden kings" - Cohen, Yoram (Brill, 2023)
"The IOS Annual volume 22: "Telling of Olden Kings" brings forth studies devoted to a wide array fields and disciplines of the Middle East. The three sections - Ancient Near East, Semitics and Arabic Language and Literature include nine articles. The Ancient Near East section is devoted exclusively to the late period of ancient Near Eastern history - Neo-Babylonian Mesopotamia and the Achaemenid Empire (Da Riva and Novotny; Levavi; Tavernier and Azzoni; Zadok). The Semitic section includes three articles dealing with contact between various languages of the Semitic language group and between Semitic languages and dialects and other language groups (Castagna; Cerqueglini; Klimiuk and Lipnicka). The Arabic section contains two articles (Khoury; Yavor)"--
Includes bibliographical references and index
Keywords: Middle East -- Languages -- Grammar, Comparative; Middle East